The Australian higher education student experience : A personal reflection on 15 years of research. - Krause, Kerri-Lee (HERDSA Review of Higher Education v.4 p.53-78, 2017)
The evolution of the Australian higher education sector began with the reforms created the unified national system in the late 1980s. Since that new policy direction Australian higher education has come of age in terms of attracting international students and widening participation in attending university. This review of the outcomes of 15 years of research identified 4 themes: student experience, interplay of research and teaching in undergraduate curriculum, monitoring and evaluating student learning, and engaging academics to engage students. As the sector confronts funding cuts to universities and the loss of supportive government agencies the review concludes there will be challenges facing those interested in rigorous and research-informed policy related to the future of the student experience. [Author abstract]